Collaborative Research Strategies for Sustainable Resource Development in Maluku: Expert Insights - Theophanny Paula Theresia Rampisela; Jonny Latuny; Devalina Lanith (CV. TOTUS TUUS, 2024)
This paper explores collaborative research strategies for sustainable natural resource development in Maluku, derived from a focus group discussion (FGD) with experts. The FGD, which included interdisciplinary collaboration and the integration of international expertise, aimed to address complex environmental challenges while incorporating local customs and ecological practices. This study highlights the benefits of such an approach, including enhanced problem-solving through diverse perspectives and advanced research methodologies. However, it also addresses potential weaknesses, such as the risk of limited local ownership and challenges in implementing proposed models within existing resource constraints. The findings emphasize the need for balancing scientific and traditional practices and ensuring that strategies are culturally sensitive and feasible. The insights from this research offer valuable guidance for developing sustainable resource management practices that are both innovative and contextually appropriate for Maluku.